Papillon-Lefevre Syndrome in a Family: A Simultaneous Occurrence in Multiple Siblings - Fatemeh Owlia; Zahra Gorji; Pegah Katiraie; Shima Mosallaei pour; Kimia Mashayekh (Journal of Mashhad Dental School, 2025)
Background: Papillon-Lefevre Syndrome (PLS) is a rare autosomal recessive disorder characterized by palmoplantar hyperkeratosis, aggressive periodontitis, and premature exfoliation of both deciduous and permanent teeth. Due to severe alveolar bone resorption, teeth are often lost two to three years after eruption, and affected individuals typically become edentulous by the age of 16-17.Case report: This study presents three siblings from the same family, each exhibiting different clinical manifestations of PLS. The first case is a 12-year-old girl who was referred to the Department of Oral Medicine with complaints of tooth mobility. She was diagnosed with severe periodontitis, permanent tooth mobility, and palmoplantar hyperkeratosis. The second case is her 10-year-old brother presenting with similar symptoms, and the third is their 9-month-old sister who had signs of palmoplantar hyperkeratosisConclusion: PLS requires early diagnosis and multidisciplinary management. Timely diagnosis and treatment can help prevent the rapid progression of disease-related complications.